Calidad de vida de los profesionales de enfermería. Distrito de Salud Chambo – Riobamba. - Cargua Alvarez, Luis Santiago (2019)
The quality of profesional life is described as the feeling of confort derived from individual balance perception, associated with the burden of the profession and the psychological, organizational and relational and interpersonal resources in the work environment. The objective was to determine the quality of nursing staff life working in Chambo-Riobamba in The Health District during the period from October 2018 to February 2019. This work had a descriptive cross – sectional study with approach, with a population of 40 nursing professionals working in the different health centers of the district, for this purpose the scale survey that measures the quality of life and satisfaction in health professionals was used, with which actions or behaviors were analyzed that directly intervene in the quality of life of the nurses, visualizing that in the simple of study the totality is conformed by single women, married and of free unión in a range of age of minors of 25 years until the 55 years until the 55 years of age, the data collected in the studies were processed with the help of an Excel database ands SPSS system, obtaining relevant data that demonstrate that there are no more prevalence of diseases in this population, being a minotity the professionals that have some type of pathological diagnosis, concluding that nursing staff has a good quality of profesional life feeling satisdied of their personal and professional life.